A Korovkin-type approximation theorem for positive linear operators in $H_{ω }\left( K\right) $ via power series method - Altiparmak, Ebru; Atlihan, Özlem Girgin (Sarajevo Journal of Mathematics, 2024)
The aim of this paper is to present Korovkin theorems for positive linear operators of two variables from $H_{ω }\left( K\right) $ into $%C_{B}\left( K\right) $ via the power series method. In addition, we give an example that our new approximation result works but its classical case does not work. Furthermore, we obtain the rate of convergence of these operators.